2009
DOI: 10.1590/s0100-29452009000300007
|View full text |Cite
|
Sign up to set email alerts
|

Disponibilidade de luz em macieiras 'Fuji' cobertas com telas antigranizo e seus efeitos sobre a fotossíntese, o rendimento e a qualidade dos frutos

Abstract: RESUMO -Em pomares de macieira, o dano de granizo pode ser evitado através da cobertura das plantas com telas. Todavia, as telas alteram a intensidade e a qualidade da luz solar e, assim, podem comprometer o rendimento e a qualidade dos frutos. Este trabalho objetivou avaliar estes aspectos em macieiras 'Fuji', cobertas com telas nas cores branca e preta. A tela preta ocasionou maiores reduções na densidade de fluxo de fótons fotossinteticamente ativos (DFFFA) disponíveis às plantas (24,8%) em relação à tela b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 7 publications
0
15
1
12
Order By: Relevance
“…Guerrero-Prieto et al (2010), Smit (2007), and Dussi et al (2005) concluded that use of a black net does not change the fruit color. However, other studies report that there is a reduction in the fruit color when grown under a net compared to those grown under the open sky (Solomakhin and Blanke 2010b; When F calculated has a value greater than F critical , there is a significant difference between the environments, p=5 % probability of error DF degrees of freedom, MS mean square Amarante et al 2009Amarante et al , 2007Jakopic et al 2007;Iglesias and Alegre 2006;Dussi et al 2005;Stampar et al 2002;Leite et al 2002). In these studies, different cultivars were used, and the fruits under the net were harvested on the same day as those under the open sky, clearly demonstrating the differences between environments.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Guerrero-Prieto et al (2010), Smit (2007), and Dussi et al (2005) concluded that use of a black net does not change the fruit color. However, other studies report that there is a reduction in the fruit color when grown under a net compared to those grown under the open sky (Solomakhin and Blanke 2010b; When F calculated has a value greater than F critical , there is a significant difference between the environments, p=5 % probability of error DF degrees of freedom, MS mean square Amarante et al 2009Amarante et al , 2007Jakopic et al 2007;Iglesias and Alegre 2006;Dussi et al 2005;Stampar et al 2002;Leite et al 2002). In these studies, different cultivars were used, and the fruits under the net were harvested on the same day as those under the open sky, clearly demonstrating the differences between environments.…”
Section: Discussionmentioning
confidence: 97%
“…Leite et al (2002) also observed a lower incidence of russeting on apples cultivated under nets, with no changes in the soluble solids, acidity, starch, or pulp firmness. However, Amarante et al (2007Amarante et al ( , 2009 observed that the cover did not influence the occurrence of russeting on apples.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A PCV foi determinada por meio de análise subjetiva da superfície com coloração vermelha nos frutos (Amarante et al, 2009b). A determinação do ângulo 'hue' (h°) da epiderme foi realizada com colorímetro modelo CR 400 (Minolta, Osaka, Japão), e as leituras foram feitas em dois lados do fruto.…”
Section: Methodsunclassified
“…Estes tipos de cobertura vêm sendo cada vez mais utilizados, e suas influências no microclima vêm sendo e devem ser estudadas, inclusive em frutíferas de clima temperado, como telas antigranizo em macieiras (LEITE et al, 2002;AMARANTE et al, 2009;CARDOSO et al, 2009;e BOSCO et al, 2010) e coberturas plásticas em vinhedos (CARDOSO et al, 2010;CHAVARRIA et al, 2007;CHAVARRIA et al, 2008;CHAVARRIA et al, 2009). Quanto ao efeito sobre o microclima, da utilização de cobertura plástica para diferentes culturas, os estudos estão sendo difundidos.…”
Section: Introductionunclassified